Vehicle occupant accommodation based on Nigerian anthropometric data - Muhammad, Abdulazeez Uba (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
A controlled selection of subjects reflecting the ethnic, age, gender and anthropometric spread of the Nigerian population similar to that undertaken by automotive companies was conducted. A total of 863 subjects comprising 460 males and 403 females participated in the exercise and 60 body dimensions applicable in automotive seat design, digital human modelling and vehicle occupant packaging were obtained using standard anthropometric instruments. The subjects were selected from the four major ethnic groups in Nigeria as well as 23 other ethnic groups reflecting the ethnic distribution of the Nigerian population. The data obtained were statistically analyzed using SPSS to obtain the necessary percentile values as well as the means and standard deviations. The results obtained were used to propose some recommendations for automotive seat fit and occupant packaging dimensions for use in the design of vehicles intended for the Nigerian market so as to ensure an optimum fit between the vehicle interior package and the occupants, as well as providing adequate accommodation. An ergonomic automotive seat suitable for the Nigerian population was designed using CATIA V5 software based on the proposed established dimensions. Six custom built Nigerian manikins were postured as drivers and passengers in a vehicle package based on CATIA V5 Human Builder vehicle occupant accommodation and another seven manikins were positioned on the seat designed for the Nigerian population. RULA ergonomic analysis conducted on all the manikins in the vehicle package both as drivers and passengers' showed that the SAE J1100 package dimensions are unsuitable for the Nigerian population with overall RULA scores between 3 to 6 for drivers and 4 to 5 for passengers. The choice of transmission type and an enhanced seat height were found to provide improved body and postural comfort for the Nigerian driver population with a difference of 1 to 3 in the final RULA scores. However, an improved seat height was found not to give enhanced body and postural comfort for most of the Nigerian passenger population with uniform overall RULA scores of 4 and 5. Finally, the seat designed for the Nigerian population proved to fit and accommodate them comfortably with acceptable RULA scores of 2 for all the seven Nigerian manikins analyzed.